UNDERSTANDING PUBLIC PERCEPTIONS OF AN IDEAL CITY IMAGE THROUGH DOUYIN: A GOVERNMENTAL REVIEW FRAMEWORK FOR XI’AN - Li , Mengjiao; Isa, Afeez Nawfal Mohd (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
Background: As short video platforms increasingly shape public discourse, public perception has become a central force in constructing and redefining city image. Cities are no longer solely defined by official narratives, but also by how they are represented and interpreted through user-generated content. Douyin, one of China’s most influential platforms, provides a valuable lens to examine how contemporary users conceptualize the characteristics of an ideal city image. Objective: This study explores how the public perceives and communicates ideal city image features on Douyin, with a specific focus on Xi’an. From a governmental perspective, it synthesizes existing city image evaluation frameworks and proposes a review model that aligns with public sentiment and platform-driven engagement dynamics. Participants and Setting: A systematic review was conducted on peer-reviewed articles published in English and Chinese between January 1, 2020, and January 1, 2025, retrieved from Scopus and CNKI databases. Inclusion criteria focused on studies related to city image evaluation, city branding, digital media’s impact on urban perception, and short video-based communication strategies. Methods: Adopting a systematic literature review approach, the study applied content analysis to categorize and evaluate existing assessment frameworks. Special attention was paid to models applicable to public-sector communication. Additionally, representative Douyin content and user interaction patterns were analyzed to reflect public perceptions of city image. Results and conclusion: As platforms like Douyin reshape urban branding in the Web 3.0 era, governments face new opportunities and challenges in understanding and managing digital city images. This study proposes a government-oriented evaluative framework that integrates traditional image indicators with digital engagement metrics, offering strategic insights for policymakers and urban communication practitioners navigating the evolving digital media landscape.